Functional Materials for Water Splitting - Balo, Figen; Sua, Lutfu S. (wiley, 2025)
Water, being plentiful in the world, is one of the most proper resources of H2 power. Through the process of water splitting, hydrogen can be produced directly from the decomposition of water into its constituents. Electrical (electricity), light (electromagnetic irradiation), or thermal (heat) energy resources can all provide the energy needed to break the H–O–H bonds. Sustainable hydrogen production is the essential prerequisite for an envisioned hydrogen economy. Due to the practical challenges faced by overall sustainable power resources, water splitting has been identified as the most suitable sustainable power resource for hydrogen production. This article first surveys current functional water splitting materials and discusses future requirements in the water splitting area. Then, considering the functional materials used for water separation in recent years, it was aimed to determine the most efficient functional material with the help of analytical hierarchy process. This study will assist in the selection of the materials’ optimal group for H2 production with water splitting for newcomers to the field, industry professionals, and specialists. © 2025 Scrivener Publishing LLC.
Keywords: AHP; H2 production; MCDM; renewable energy; Water splitting